Manoeuvring into the Soviet market. Polish and Finnish Eastern trade practices during the Cold War - Kansikas Suvi; Oiva Mila; Matala Saara (Routledge, 2022)
This chapter studies Polish and Finnish traders' efforts to access the Soviet market. By analysing socialist Poland's clothing industry and capitalist Finland's shipbuilding industry access to the Soviet market, the study sheds light onto foreign trade practices of smaller states that sought to increase their room to manoeuvre in an asymmetric trade political situation. Agency of the smaller powers is analysed in three phases of commerce: market analysis, marketing, and political lobbying. The article focuses on individuals (entrepreneurs) and intermediate-level actors (Finland, Poland); private businesses (Finland) and state-owned foreign trade organisations (Poland). The chapter reveals that a sale onto the Soviet market took place within a set of political, economic, structural, social and cultural margins for manoeuvring. The rigidities as well as the loopholes of the planned economy formed the structures in which the actors operated. The article studies whether the two countries used similar strategies to sell their products to the Soviet buyers. It suggests that their relative leverage was related to their perceived westernness compared to the USSR and agility to respond to Soviet demand. With successful business deals both actors gained, besides economic benefit, also sovereignty vis-a-vis the Soviet Union.
Margins for Manoeuvre in Cold War Europe. The Influence of Smaller Powers